Differential contribution of soil biota groups to plant litter decomposition as mediated by soil use - Ricardo A. Castro-Huerta; Liliana B. Falco; Rosana V. Sandler; Carlos E. Coviella (PeerJ, 2015)
Plant decomposition is dependant on the activity of the soil biota and its interactions with climate, soil properties, and plant residue inputs. This work assessed the roles of different groups of the soil biota on litter decomposition, and the way they are modulated by soil use. Litterbags of different mesh sizes for the selective exclusion of soil fauna by size (macro, meso, and microfauna) were filled with standardized dried leaves and placed on the same soil under different use intensities: naturalized grasslands, recent agriculture, and intensive agriculture fields. During five months, litterbags of each mesh size were collected once a month per system with five replicates. The remaining mass was measured and decomposition rates calculated. Differences were found for the different biota groups, and they were dependant on soil use. Within systems, the results show that in the naturalized grasslands, the macrofauna had the highest contribution to decomposition. In the recent agricultural system it was the combined activity of the macro- and mesofauna, and in the intensive agricultural use it was the mesofauna activity. These results underscore the relative importance and activity of the different groups of the edaphic biota and the effects of different soil uses on soil biota activity.